Adiciones a las aves de la comisaria del vaupés (colombia), ii (1964)
With this paper the following species and subespecies are added to the Colombian ornis: Nyctiprogne latifacia Phaethornis b. bourcieri Dendrocincla merula bartletti Gymnopithys leuscaspis lateralis Rhegmatorhina cristata Neopelma chrysocephalum Myiophobus roraimae Platyrinchus senex griseiceps Platyrinchus saturatus Hylocharis cyaneus viridiventris and Setophaga ruticila tricolora are registered for first time in the Cisandean region of Colombia; the presence of Trogon m. melanurus is confirmed in the country; 57 new species and subespecies are noted for the Comisaría del Vaupés in which territory the collection of birds studied in this publication was made. In that region of Colombia new localities were under survey, namely. Sabanas del Cubiyú and Caños Cubiyú and Negro of which a geographical and ecological description is given in the introduction. Previous publications containing geographical and ornithological information on the Vaupés are: Olivares (1955), Olivares and Hernández (1962) and Olivares (1964).